Leveraging Bulk and Single-Cell RNA Sequencing Data of NSCLC Tumor Microenvironment and Therapeutic Potential of NLOC-15A, A Novel Multi-Target Small Molecule - Lawal, Bashir; Wu, Alexander T. H.; Huang, Hsu-Shan (Frontiers in Immunology, 2022)
Lung cancer poses a serious threat to human health and has recently been tagged the most common malignant disease with the highest incidence and mortality rate. Although epidermal growth factor (EGFR)-tyrosine kinase inhibitors (TKIs) have significantly improved the prognosis of advanced non-small cell lung cancer (NSCLC) patients with EGFR mutations, patients often develop resistance to these drugs. There is therefore a need to identify new drug candidates with multitarget potential for treating NSCLC. We hereby provide preclinical evidence of the therapeutic efficacy of NLOC-015A a multitarget small-molecule inhibitor of EGFR/mitogen-activated protein (MAP) kinase kinase 1 (MAP2K1)/mammalian target of rapamycin (mTOR)/yes-associated protein 1 (YAP1) for the treatment NSCLC. Our multi-omics analysis of clinical data from cohorts of NSCLC revealed that dysregulation of EGFR/MAP2K1/mTOR/YAP1 signaling pathways was associated with the progression, therapeutic resistance, immune-invasive phenotypes, and worse prognoses of NSCLC patients. Analysis of single-cell RNA sequencing datasets revealed that MAP2K1, mTOR, YAP1 and EGFR were predominantly located on monocytes/macrophages, Treg and exhaustive CD8 T cell, and are involved in M2 polarization within the TME of patients with primary and metastatic NSCLC which further implied gene’s role in remodeling the tumor immune microenvironment. A molecular-docking analysis revealed that NLOC-015A bound to YAP1, EGFR, MAP kinase/extracellular signal-related kinase kinase 1 (MEK1), and mTOR with strong binding efficacies ranging –8.4 to –9.50 kcal/mol. Interestingly, compared to osimertinib, NLOC-015 bound with higher efficacy to the tyrosine kinase (TK) domains of both T790M and T790M/C797S mutant-bearing EGFR. Our in vitro studies and sequencing analysis revealed that NLOC-015A inhibited the proliferation of NSCLC cell lines with concomitant downregulation of expression levels of mTOR/NF-κB, YAP1, MEK1 signaling network. We, therefore, suggest that NLOC-015A might represent a new candidate for treating NSCLC via acting as a multitarget inhibitor of EGFR, mTOR/NF-κB, YAP1, MEK1 in NSCLC.